Tool orientation optimization for the five-axis CNC machining to constrain the contour errors without interference. (April 2022) - Xiao, Qun-Bao; Wan, Min; Zhang, Wei-Hong; Yang, Yun
Abstract: Tool orientation optimization with interference-free condition and good machining performance is one of the key issues in the five-axis machining processes. The existing tool orientation optimization algorithms usually reduce the contour errors indirectly through reducing each order derivative of the trajectory. In this article, a tool orientation optimization algorithm, which achieves the direct constraining of the tool tip and tool orientation contour errors while avoiding the interference between the tool and workpiece, is proposed for the first time. Two prediction models, i.e. an analytical model and a numerical model, are developed to predict the contour errors according to the tool orientation splines. Through considering multiple factors such as the real feedrate, the dynamics of the servo control system, the friction disturbance torque, the velocity, acceleration and jerk of the servo axes, the developed prediction models realize the precise prediction of contour errors. Through transforming the contour errors constraints and interference-free constraints into penalty terms, the constrained optimization problem is transformed to an unconstrained problem. Experiments validate that through optimizing the tool orientations, the maximum tool tip and tool orientation contour errors can be reduced by 52.2% and 75.6%.